What is the Scope and Nature of Studies Exploring the Relationship Between Boredom and Substance Use Among Persons Who are Unhoused in Existing Peer-reviewed Literature? - Herzog-Fequet, Cory; Gewurtz, Rebecca; Hansen, Noah; Read, Halley; Ward, Brooklyn; Marshall, Carrie (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Background: Research consistently provides evidence of an association between substance use and the experience of boredom, but how this relationship works is poorly understood. Purpose: The scope of literature exploring the relationship between boredom and substance use among persons who are unhoused is unknown. This study was employed to amalgamate this literature. Method: We conducted a scoping review using Arksey and O’Malley’s (2005) framework, supplemented by the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. Using pre-established inclusion and exclusion criteria, two independent raters performed a title and abstract screening followed by a full-text review of all applicable articles. An inductive data analysis was then performed. Findings: The search yielded 581 articles after the removal of duplicates. A total of seven articles remained at the full-text review stage and were included in the narrative synthesis. Four Themes were identified: 1) bored and homeless- the social aspects of ongoing substance use; 2) the provision of social and recreational activities as the antithesis to boredom and substance use; 3) substance use as a means of coping with boredom; and 4) the detrimental effects of substance use as a way of coping with boredom. None of the included studies specifically set out to examine the relationship between boredom and substance use among persons who were unhoused, suggesting a gap in the literature. Implications: A more fulsome understanding of the relationship between boredom and substance use is needed, particularly for persons who are unhoused, given the high prevalence of substance use in this population.